Seasonal Variation in the Intake of Food Groups and Nutrients in Japan: A Systematic Review and Meta-analysis - Riho Adachi; Fumi Oono; Mai Matsumoto; Xiaoyi Yuan; Kentaro Murakami; Satoshi Sasaki; Hidemi Takimoto (Journal of Epidemiology)
Background: Seasonal variations could systematically bias dietary intakes. This systematic review aimed to determine seasonal variations in dietary intake among Japanese adults. Methods: PubMed and Ichushi-Web databases were searched for studies reporting seasonal intakes of nutrients or food groups assessed using dietary records or 24-hour recalls. The protocol was registered with PROSPERO (CRD42022356084). Results: Ten studies (eight studies on 1–31 nutrients and four on 2–15 food groups) met the inclusion criteria. Six studies included both sexes, whereas four investigated only females. The number of participants ranged from 25 to 459, and the number of dietary survey days in each season ranged from 1 to 14. For most nutrient and food groups, the reported seasonal variations were inconsistent across studies. The meta-analyses comparing differences in mean intakes between two seasons showed no significant differences in all comparisons or differences in only one comparison for most nutrients and food groups. Significant seasonal differences were observed for vegetables, fruits, and potatoes in five out of six comparisons, though the heterogeneity was high. Their biggest differences were as follows: 101 g/day more vegetable intake in summer than spring, 60 g/day more fruit intake in fall than spring, and 20.1 g/day more potato intake in fall than spring. Conclusion: Reported seasonal variations were inconsistent across studies for most food groups and nutrients. Relatively distinct seasonal differences in mean intakes were observed for vegetables, fruits, and potatoes in meta-analyses. However, these results must be interpreted cautiously because of the high heterogeneity and limited representativeness.